The importance of multiple intelligences applied in teaching english as a foreign language in the intermediate english courses at the FLD, semester II-2012 - Arucha Chicas, Ana Lilian; Corado Alvarenga, Karla Margarita; Rosales Bernal, Claudia Patricia; Vides de Guzmán, Claudia Marina; Garay Salinas, Ricardo (San Salvador, El Salvador : Universidad de El Salvador, 2013)
This research project is focused on the investigation of the Multiple Intelligences theory applied in EFL (English as a Foreign Language) classrooms. It is based on the Theory of Multiple Intelligences proposed by Psychologist Howard Gardner on The Frames of Mind(1983, 1993) and on studies made by Bruce Campbell (1990), Thomas Armstrong (1994) and Mary Ann Christison (2005). The main purpose of this research project was to analyze the importance of the Multiple Intelligences theory applied in teaching English as a foreign language in the Intermediate English l courses. One of the aspects that this research attempted to find was if the activities teachers developed in their lessons are in agreement with the intelligences students possess. It also tried to identify which activities are carried out in the class to develop the 8 intelligences given by Howard Gardner. The researchers have also attempted to provide strategies, techniques and activities that teachers of the skills’ development area could use to reinforce the intelligences students have in order to help them in their teaching-learning process so that EFL students can improve their academic performance.
Anexos.
Tesis -- (Licenciatura en Lenguas Modernas especialidad Francés e Inglés) -- Universidad de El Salvador, San Salvador, 2013
Referencias : hojas 98-100
Audiencia general
La tesis está en formato digital.
Texto en Inglés
Keywords: Inglés -- Enseñanza; Lenguaje y lenguas -- Enseñanza; Inteligencias múltiples